Дослідження показника мережевої релаксації як характеристики вузлів мережі - Ланде, Д.В.; Дмитренко, О.О.; Снарський, А.О. (Реєстрація, зберігання і обробка даних, 2019)
Робота присвячена дослідженню нової характеристики вузлів мережевих структур — показнику релаксації. Установлено, що на відновлення окремих уже традиційних показників мережі, після збурення окремих вузлів, впливає її топологія. Показник релаксації було використано для дослідження структури мережі термів, що побудована для предметної області «інтернет-речей». Завдяки застосуванню показника релаксації вдалося визначити найбільш важливі компоненти мережі. Работа посвящена исследованию новой характеристики узлов сетевых структур — показателю релаксации. Установлено, что на восстановление отдельных уже традиционных показателей сети, после возмущения отдельных узлов, влияет ее топология. Показатель релаксации был использован для исследования структуры лингвистической сети, построенной для предметной области «интернет-вещей». Благодаря применению показателя релаксации удалось определить наиболее важные компоненты сети. The article is devoted to the research of a new characteristic of the nodes of network structures — the relaxation time. HITS and PageRank algorithms are used for research relaxation time of nodes after giving them a perturbation. It was found that the relaxation of some already traditional indicators of network, after the perturbation of individual nodes, is affected by its topology, namely: the absence or presence of outgoing links in the perturbed nodes and their number; the presence of outgoing links in perturbed nodes, which are only «authors»; the presence of outgoing links to nodes that are primary sources of «important» nodes; the presence of «authoritative» nodes that refer to a perturbed node; the entry of the disturbed node into a separate small cluster, etc. The relaxation time was used to research the structure of the language network that built for the subject domain «Internet of things». In this study, an algorithm for forming a directed network of words and word combinations - an algorithm for forming network of natural terms hierarchy (NNTH) was used for building the language network. By using of the relaxation time the most important components of the network that related with the subject domain «Internet of things» were determined. The numerical characteristic of network nodes, which suggested in the study can be used for researching and analyzing the structure of the network, and enable to identify of the most important and structural elements.